1970
DOI: 10.3329/jbs.v16i0.3749
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid function in Bangladeshi Patients with Vitiligo (Sheti)

Abstract: Serum thyroid hormone levels have been assayed to evaluate the thyroid hormonal function in Vitiligo patients of Bangladesh. The levels of TSH, T3 and T4 in the serum of Vitiligo patients have been analyzed in both the male and female subjects. Results of hormonal assay indicated that some hormonal changes occurred in the Vitiligo patients as compared with the healthy control. In female Vitiligo patient's, TSH level was increased remarkably as compared to the control male patients, but T3 and T4 became lower t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Various studies on Vitiligo suggest that there is a significant association between Vitiligo and other disease 174 Study of some biochemical parameters of vitiligo 47(2) 2012 1970) may also be found, it up 30 to 40 percent (Howanitz et al 1981). It has been reported that the thyroid function has been elevated in women and children (Amin et al 2008). Diabetes mellitus both juvenile and adult onset types occur in 1 to 7.1 percent of Vitiligo patients and conversely, Vitiligo occurs in 4.8 percent of diabetes patients (Ghoeum et al 1987).…”
Section: Introductionmentioning
confidence: 94%
“…Various studies on Vitiligo suggest that there is a significant association between Vitiligo and other disease 174 Study of some biochemical parameters of vitiligo 47(2) 2012 1970) may also be found, it up 30 to 40 percent (Howanitz et al 1981). It has been reported that the thyroid function has been elevated in women and children (Amin et al 2008). Diabetes mellitus both juvenile and adult onset types occur in 1 to 7.1 percent of Vitiligo patients and conversely, Vitiligo occurs in 4.8 percent of diabetes patients (Ghoeum et al 1987).…”
Section: Introductionmentioning
confidence: 94%